An Overview of Work Ability of Employees Using Artificial Intelligence: A Phenomenological Study - Renata Noorawhita (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2026)
Objective – The use of technology such as artificial intelligence in the workplace can change and reshape the job market, especially in terms of skills and knowledge that influence a person's work ability. This study aims to describe the work ability of workers after using AI in their work. Design/Methodology/Approach – This research design uses a phenomenological approach and is conducted through semi-structured interviews, which are then analyzed using IPA. Sample selection is done using the snowball sampling technique. Interviews are conducted with 3 participants face-to-face. Findings – The results of the interview analysis produce four themes in describing the work ability of workers, namely (1) perception of work effectiveness and efficiency using AI; (2) perception of the need for knowledge and skills development; (3) self-evaluation of AI use behavior; and (4) feelings after making decisions using AI. Implications – This research provides an overview of the challenges faced in the era of the industrial revolution based on artificial intelligence technology so that it can help prospective workers, employees, and employers to prepare the knowledge and skills needed and help to maintain their abilities and performance.